Development of Urdu version of Chronic Respiratory Disease Questionnaire Self-Administered Standardized (CRQ-SAS); validity and reliability analysis in COPD patients. - Momina Kashif; Danish Hassan; Saira Khalid; Syed Shakil Ur Rehman; Nimra Noor (PLoS ONE, 2023)
Purpose Chronic Respiratory Disease Questionnaire Self-Administered Standardized (CRQ-SAS) is a valid and reliable tool that evaluates the health-related quality of life among the adult population affected with chronic respiratory disorders (CRDs) and has been translated into many languages as per need. The main objective of this study was to translate the CRQ-SAS into the Urdu language and evaluate its psychometric properties. Methodology It was a two-staged study that consisted of translating the original version into Urdu language and then psychometric testing of the translated version. The reliability of the translated questionnaire was assessed by measuring its internal consistency, test-retest reliability, standard error of mean (SEM) & minimal detectable change (MDC). Validity was determined by evaluating its content for content validity, construct (convergent and discriminative) validity, and exploratory factor analysis. Data was analyzed using SPSS v 28 with an alpha level < 0.05 considered to be significant. Results CRQ-SAS U had an excellent internal consistency (Cronbach's Alpha α = 0.89), test-retest reliability (ICC2,1) = 0.91 of all items, and low SEM = 0.11 and MDC = 0.65. S-CVI was 0.9, with statistically significant difference across the response of COPD patients and healthy subjects, and a high degree of correlation with St Georges Respiratory Questionnaire (r = 0.7-0.9) proving CRQ-SAS U content, discriminant and convergent valid respectively. Exploratory factor analysis identified two factors responsible for 80% of the variance. Conclusion CRQ-SAS U demonstrated optimal psychometric properties which renders it to be used in Urdu speaking populations with COPD.